PENGARUH ASAM SULFAT TERHADAP PRODUKTIVITAS GETAH PINUS DENGAN SISTEM KOAKAN DI KPHL VI SIPIROK KECAMATAN SIPIROK KABUPATEN TAPANULI SELATAN SUMATERAUTARA - Susilastri Susilastri (Ensiklopedia of Journal, 2023)
Production forest is forest area that is deliberatery maintained as forest area and for the benefit of the community in the industrial and export sectors. If seen from understanding production fprest, pine is one growing plants in production forest in the area KPHL VI Sipirok, Sumatera Utara pine produces sap at age eleven years, harvesting pine sap is done by tapping Idris and Soenarno (1983) According to outline there are three systems tapping pine resin that is koakan, corporal, and drill.The purpose of this research is to know effect of sulfuric acidon (H2SO4). On production of pine resin with system  koakan. Research using the method quantitative, statistics with randomized block design,  direct observation to the field and documentation. Tree used diameter 20-25 cm and 26-30 cm with treatment adittion of sulfuric acid and without sulfuric acid, with a total of 12 observation trees, pine resin productivity in creases after adding sulfuric acid, productivity of pine resin with addition of diameter sulfuric acid 20-25 cm produce as much sap 747 grams/month and diameter 26-30 cm produced as muchsap 777,9 grams/month. Pine resin productivity without treatment with diameters 20-25 cm produce as much sap 187 grams/month and diameters 26-30 cm as much 196,5 grams/month. From the test results randomized group design productivity of pine resin on the difference result of productivity value of pine resin from the analysis of randomized bloc design stated significantly different of randomized bloc design stated significantly different on class diameters 20-25 cm and 26-30 cm to different treatment using sulfuric acid and without sulfuric acid this can be seen from the value of F count > F table on the source of the diversity of treatments whereas at the source of group diversity was not significantly different can be see from the carculated F value< F table.Keyword: Pine Sap, Koakan System, Sulfuric Acid